Estudio de la producción beneficiado y comercialización de cacao para el sector Luz y Guía - Flores Aguacondo, Yenry Emilio (2006)
The present work is part of those “definitive Studies of the Subproyecto Intercantonal of benefitted production and commercialization of cocoa in the low areas of Pucará, Ponce Enríquez and Pijilí”, proposal that it is developing in Agreement with the M. I. Municipality of Ponce Enríquez, The University of Machala and the Fundación Progreso and Desarrollo PRODE, the project is financed by the PROLOCAL and it will be presented to Desarrollo IDB'S Interamerican Bank. OBJECTIVES: FOR THE COMPONENT OF: “I study of the productive offer and commercialization cacaotera: 3. To diagnose the productive and commercial offer. 4. To propose the improvement continues of the productive system, and of the ommercialization system. FOR THE COMPONENT OF: “Partner - Organizational–Self-management”: 3. To diagnose the structure organizational beneficiary. 4. To outline a structure partner–organizational for viabilizar the installation of the project, with the support of a system of active, equal participation and empoderada with all and each one of the potential partners of the sub one. - project. As a result of the integral diagnosis of the productive and commercial offer he/she comes off that the drop productivity of the Sector Luz and it Guides it is of 6.11 qq/ha (fresh + dry); against 8.2 qq/promedio/país and 10 qq average in the area of Orange grove, the goal to the two years of intervention of the project a production of 9 qq /ha/año will be gotten in the Sector Luz and it Guides that it will be competitive for the producing cacaoteros. For the component of partner-organizational invigoration he/she has a weakness of 30% the same one that has been planned to qualify to the farmers and the necessity of forming a community that has artificial life. The intervention proposal is planned for two years of an intensive training process and technical attendance, it will allow to improve the production levels, to implement the proposal of direct commercialization, the middlemen that absorb a great margin of utility without carrying out any investment type, eliminating for it will be implemented it a storing center located in Shagal and administered by the same organization.